The allele 4 of neck region liver-lymph node-specific ICAM-3-grabbing integrin variant is associated with spontaneous clearance of hepatitis C virus and decrease of viral loads - Ezzikouri, S.; Rebbani, K.; Fakhir, F.-Z.; Alaoui, R.; Nadir, S.; Diepolder, H.; Thursz, M.; Khakoo, S.I.; Benjelloun, S. (Clinical microbiology and infection, 2014)
L-SIGN is a C-type lectin expressed on liver sinusoidal endothelial cells involved in the capture of hepatitis C virus and trans-infection of adjacent hepatocyte cells. The neck region of L-SIGN is highly polymorphic, with three to nine tandem repeats of 23 residues. This polymorphism is associated with a number of infectious diseases, but has not been explored in HCV. We therefore investigated the impact of L-SIGN neck region length variation on the outcome of HCV infection. We studied 322 subjects, 150 patients with persistent HCV infection, 63 individuals with spontaneous clearance and 109 healthy controls. In healthy subjects, we found a total of nine genotypes, with the 7/7 genotype being the most frequent (33%) followed by the 7/6 (22.9%) and the 7/5 (18.3%). The frequencies of the alleles were as follows: 7-LSIGN (56.4%), 6-LSIGN (20.2%), 5-L-SIGN (18.3%) and 4-L-SIGN (5%). The frequency of the 7/4 genotype was higher in spontaneous resolvers (14.3%) as compared with the persistent group (4%) (OR = 0.25, 95% CI = 0.07–0.82, p 0.022). In addition, we found that 4-L-SIGN was associated with spontaneous resolution of HCV infection (OR = 0.30, 95%CI, 0.12–0.74, p 0.005). Interestingly, patients with 4-L-SIGN had lower viral loads when compared with carriers of the 5 (p 0.001), 6 (p 0.021) and 7-alleles (p 0.048). The results indicate that neck region polymorphism of L-SIGN can influence the outcome of HCV infection and the four-tandem repeat is associated with clearance of HCV infection.